2020
DOI: 10.21687/0233-528x-2020-54-5-73-76
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Antihypoxic Properties of New Nicotinic Acid Derivatives

Abstract: Two of the five new nicotinic acid derivatives proved to have the antihypoxic properties in tests with mice exposed to acute normobaric hypoxic hypoxia with hypercapnia. Specifically, LKhT 4–19 (100 mg/kg) extended lifetime of the animals by 11 %; LKhT 6-19 doses of 50 and 100 mg/kg extended lifetime by 23 and 34 %, respectively. The antihypoxic effect of LKhT 6–19 (50 mg/kg) outperformed in 1.2 times mexidol (substance of comparison) at the similar dose and was highly competitive at the dose of 100 mg/kg. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The choice of doses of the studied compounds was dictated by the results of previous experiments, in particular, to study their antihypoxic activity (Yasnetsov et al 2020).…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of doses of the studied compounds was dictated by the results of previous experiments, in particular, to study their antihypoxic activity (Yasnetsov et al 2020).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…We have previously shown that one of the five new nicotinic acid derivatives, LKhT 6-19, was the most efficient on a model of acute hypoxia in a hermetic chamber in mice. This derivative provided an action depending on the dose, surpassing the severity of the effect of the wellknown domestic drug mexidol (Yasnetsov et al 2020).…”
Section: Introductionmentioning
confidence: 99%